Why people matter in ocean governance: Incorporating human dimensions into large-scale marine protected areas. (October 2017) - Christie, Patrick; Bennett, Nathan J.; Gray, Noella J.; 'Aulani Wilhelm, T.; Lewis, Nai'a; Parks, John; Ban, Natalie C.; Gruby, Rebecca L.; Gordon, Lindsay; Day, Jon; Taei, Sue; Friedlander, Alan M.
Abstract: Large-scale marine protected areas (LSMPAs) are rapidly increasing. Due to their sheer size, complex socio-political realities, and distinct local cultural perspectives and economic needs, implementing and managing LSMPAs successfully creates a number of human dimensions challenges. It is timely and important to explore the human dimensions of LSMPAs. This paper draws on the results of a global "Think Tank on the Human Dimensions of Large Scale Marine Protected Areas" involving 125 people from 17 countries, including representatives from government agencies, non-governmental organizations, academia, professionals, industry, cultural/indigenous leaders and LSMPA site managers. The overarching goal of this effort was to be proactive in understanding the issues and developing best management practices and a research agenda that address the human dimensions of LSMPAs. Identified best management practices for the human dimensions of LSMPAs included: integration of culture and traditions, effective public and stakeholder engagement, maintenance of livelihoods and wellbeing, promotion of economic sustainability, conflict management and resolution, transparency and matching institutions, legitimate and appropriate governance, and social justice and empowerment. A shared human dimensions research agenda was developed that included priority topics under the themes of scoping human dimensions, governance, politics, social and economic outcomes, and culture and tradition. The authors discuss future directions in researching and incorporating human dimensions into LSMPAs design and management, reflect on this global effort to co-produce knowledge and re-orient practice on the human dimensions of LSMPAs, and invite others to join a nascent community of practice on the human dimensions of large-scale marine conservation.